The Effect of Brain Jogging Exercise on The Attention Ability of Students in Class VIII of SMP Negeri 9 Bandung - Heryanto, Mamat; Sholehudin, Indra (Journal of Physical and Outdoor Education, 2023)
The purpose of this study was to determine the effect of brain jogging exercises on cognitive abilities, especially memory and attention abilities. The method used in this research is the pre-experimental method with a one group pretest-posttest design. The sampling technique used in this study is the cluster random sampling technique. The sample in this study were 29 students of Class VIII 8 of SMP Negeri 9 Bandung. The instrument used in this study was the Concentration Grid Test to measure students' attentional abilities. The results of the analysis of data processing showed that there was an effect of brain jogging exercises on attentional abilities (t=5.215 p=.000). The conclusions in the study showed that there was a significant effect of brain jogging exercises on the attention abilities of Grade VIII students of SMPN 9 Bandung